The invasive kelp Undaria pinnatifida (Phaeophyceae, Laminariales) reduces native seaweed diversity in Nuevo Gulf (Patagonia, Argentina) - Casas, Graciela Noemi (2004)
The kelp Undaria pinnatifida (Phaeophyceae) is a seaweed native to northeast Asia, but during the last two decades, it has been accidentally or intentionally introduced in several temperate coasts worldwide. In central Patagonia (Argentina), this species was first detected in late 1992, and it is progressively spreading from the point of introduction. Through a manipulative experiment involving Undaria removal in 2001, we found that its presence is associated with a dramatic decrease in species richness and diversity of native seaweeds in Nuevo Gulf. Future prospects are worrisome, as, in addition to the negative impact from a biodiversity viewpoint, native commercial macroalgae and invertebrates might also be affected.